Different isolation methods alter the gene expression profiling of adipose derived stem cells - Gnanasegaran, N.; Govindasamy, V.; Musa, S.; Abu Kasim, N.H. (Ivyspring International Publisher, 2014)
Human adipose stem cells (ASCs) has been in the limelight since its discovery as a suitable source of mesenchymal stem cells (MSCs) in regenerative medicine. Currently, two major techniques are used to isolate ASCs, namely liposuction and tissue biopsy. These two methods are relatively risk-free but the question as to which method could give a more efficient output remains unclear. Thus, this study was carried out to compare and contrast the output generated in regards to growth kinetics, differentiation capabilities in vitro, and gene expression profiling. It was found that ASCs from both isolation methods were comparable in terms of growth kinetics and tri-lineage differentiation. Furthermore, ASCs from both populations were reported as CD44+, CD73+, CD90+, CD166+, CD34-, CD45- and HLA-DR-. However, in regards to gene expression, a group of overlapping genes as well as distinct genes were observed. Distinct gene expressions indicated that ASCs (liposuction) has endoderm lineage propensity whereas ASCs (biopsy) has a tendency towards mesoderm/ectoderm lineage. This information suggests involvement in different functional activity in accordance to isolation method. In conclusion, future studies to better understand these gene functions should be carried out in order to contribute in the applicability of each respective cells in regenerative therapy.